Awareness of Angina And Its Associated Risk Factors Among The General Population In Jeddah City - Hafiz, Alaa; Alharbi, Elaf; Rabei, Sara; Ahmed, Faridah; Katooa, Nouran Essam; Abunar, Areej (Journal of Neonatal Surgery, 2025)
Introduction: Angina, characterized by chest pain, is a common symptom of coronary artery disease (CAD) and occurs when there is inadequate blood flow to the heart muscle. Early recognition of angina and managing risk factors such as hypertension and smoking are vital for preventing cardiovascular complications. CAD contributes significantly to global cardiovascular disease deaths, especially in GCC countries. Despite global efforts, studies conducted in various nations, including Syria, Cameroon and Oman have consistently highlighted a lack of awareness regarding cardiovascular disease (CVD) risk factors and symptoms among populations. However, there is limited studies assessing the current level of awareness regarding angina and its associated risk among the general population in Jeddah. This information will be crucial in developing targeted interventions to improve overall awareness and prevention of cardiovascular diseases (CVDs) in Jeddah and the surrounding areas. Aim: This research aims to investigate the current level of awareness regarding angina and its associated risk factors among the general population in Jeddah. Methodology: A quantitative, cross-sectional, and descriptive research approach was applied. Results: The study included 385 participants, predominantly single individuals from North Jeddah with at least a bachelor's degree. 59.9% demonstrated good awareness of (CVD) risk factors. Regarding clinical picture understanding, 42.2% showed good awareness, while 92.1% were knowledgeable about CVD prevention. Significant associations were observed between awareness levels, age, and gender, with males and younger participants exhibiting higher awareness levels. Conclusion: The findings revealed a range of awareness levels, with some recognition of the risk factors associated with angina. Specifically, identified significant gaps in understanding the symptoms of angina. Ongoing efforts are needed to address knowledge gaps, especially among specific groups, through tailored public health strategies and education